2016
DOI: 10.1111/bcp.12829
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and antipsychotics classified with torsades de pointes arrhythmia risk and mortality in older adults ‐ a Swedish nationwide study

Abstract: AIMThe aim of the study was to examine mortality risk associated with use of antidepressants and antipsychotics classified with torsades de pointes (TdP) risk in elderly. METHODSA matched case-control register study was conducted in people 65 years and older dying outside hospital from 2008-2013 (n = 286 092) and matched controls (n = 1 430 460). The association between prescription of antidepressants and antipsychotics with various TdP risk according to CredibleMeds (www.crediblemeds.org) and all-cause mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 43 publications
2
37
0
4
Order By: Relevance
“…When the BNF sections are categorized into different types of comorbidity medications (Table 3), those on anti-arrhythmic and diabetic medication had significantly higher mortality rates in comparison to PwD with no comorbidities. Although this finding should be interpreted with caution, as it is a proxy measure rather than an official diagnosis of the comorbidities, the findings dovetail those of recent studies which suggest that those with diabetes and arrhythmic conditions have higher mortality rates [36,37]. Moreover, PwD who have also been diagnosed with dementia have poorer medication management and are less likely to receive the recommended annual monitoring for diabetes than people without dementia [38].…”
Section: Discussionsupporting
confidence: 71%
“…When the BNF sections are categorized into different types of comorbidity medications (Table 3), those on anti-arrhythmic and diabetic medication had significantly higher mortality rates in comparison to PwD with no comorbidities. Although this finding should be interpreted with caution, as it is a proxy measure rather than an official diagnosis of the comorbidities, the findings dovetail those of recent studies which suggest that those with diabetes and arrhythmic conditions have higher mortality rates [36,37]. Moreover, PwD who have also been diagnosed with dementia have poorer medication management and are less likely to receive the recommended annual monitoring for diabetes than people without dementia [38].…”
Section: Discussionsupporting
confidence: 71%
“…Considering that most elderly patients have numerous risk factors for TdP at baseline, the assessment of these, including electrocardiographic screening, should be carried out routinely by physicians before and after starting any drug that could prolong the QT interval . In the present study, diuretics (furosemide and hydrochlorothiazide) were the most commonly prescribed QT‐prolonging drugs and therefore their use requires close monitoring, especially because of their hypokalaemic effect and associated cardiovascular comorbidity.…”
Section: Discussionmentioning
confidence: 96%
“…High doses of such drugs are especially dangerous for women because they possess a relatively greater lipid : lean ratio and therefore more space for drug accumulation . A recent case‐control study of Swedish elderly patients consuming antidepressant and antipsychotic drugs showed that patients using drugs with a known or possible risk of TdP are at higher risk for mortality compared with drugs with a conditional risk or without a TdP classification .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, elongation of the QT interval, torsade de pointes (TdP), and sudden cardiac death have a known relationship with antipsychotic drugs (Sicouri and Antzelevitch, 2018). A case control study on a population aged 65 years or above, undertaking antipsychotics at possible or conditional risk of TdP, demonstrated higher TdP risk for drugs classified as "known TdP risk, " with risk ranking of haloperidol > risperidone > olanzapine > quetiapine (Danielsson et al, 2016). The risk of VTE is estimated to be double, compared to the general population, especially within the first three months of therapy, and several mechanisms are potentially responsible for this association.…”
Section: Antipsychotics and Safetymentioning
confidence: 99%